ChemInform Abstract: Highly Enantioselective Iron(II)‐Catalyzed Opening Reaction of Aromatic meso‐Epoxides with Indoles. Issue 12 (25th March 2014) - Plancq, Baptiste; Lafantaisie, Mathieu; Companys, Simon; Maroun, Cendrella; Ollevier, Thierry
Abstract Unprecedented high enantioselectivities are obtained in the ring opening of cis‐stilbene oxide (II) with indoles (I) using iron perchlorate and a chiral bipyridine ligand as catalyst system.